In Pursuit of the Epithelial Mechanosensitivity Mechanisms - Beyder, Arthur (Frontiers in Endocrinology, 2019)
Mechanosensation, or awareness of mechanical forces, is critical for normal gastrointestinal (GI) function. Disruption in GI mechanosensation leads to human diseases. Mechanical forces in the GI tract are sensed by several dedicated, or specialized, mechanosensory cell types, and these cellular mechanosensors orchestrate physiologic responses. GI epithelium is at the interface of the body and the environment. It encounters a variety of mechanical forces that range from shear stress due to flow of luminal contents to extrinsic compression due to smooth muscle contraction. Mechanical forces applied to the GI mucosa lead to a large outflow of serotonin, and since serotonin is concentrated in a single type of epithelial cell, called enterochromaffin (EC) cell. Recent studies show that a subset of EC cells is indeed mechanosensitive and that Piezo2 mechanosensitive ion channels are necessary for coupling force to serotonin release. This review aims to place this mechanism into the larger context of EC cell mechanotransduction, and to ask what GI mechanical forces are relevant for EC cell function.